Characteristics of expression of proteomic markers in women with "thin" endometrium and their importance for the therapeutic effects of the use of exogenous estradiol: A prospective cohort comparative study - Natalia V. Aganezova; Sergey S. Aganezov; Ksenia E. Gogichashvili (IP Berlin A.V., 2024)
Aim. To analyze the relationship between the expression of proteomic markers [estrogen (ER) and progesterone (PR) receptors, LIF, FOXA1, FOXA2] of endometrial receptivity and indicators of the levels of sex steroids [estradiol (E2) and progesterone (P)] in the peripheral blood during the "implantation window" in women with a history of reproductive dysfunction with "thin" endometrium (TE) and evaluate their significance for the therapeutic effect of using estradiol drugs. Materials and methods. The prospective cohort comparative study was conducted. The main group included 52 patients with TE (7 mm according to ultrasound on preovulatory days), the comparison group consisted of 62 women with normal endometrial thickness (≥7 mm according to ultrasound), women of both groups with reproductive dysfunctions of unknown reason; the control group included 16 healthy women. Aspiration biopsy of the endometrium was performed on the 6-8 days after ovulation (LH +6-8), as well as venipuncture to obtain a sample of peripheral blood to determine the E2, P levels. A combined histological and immunohistochemical study of endometrial samples was performed (ER, PR, LIF, FOXA1, FOXA2). The therapeutic effects of estradiol drugs were assessed in a cohort of women from the main group with TE (n=16 out of 26, those who have not changed their reproductive plans). Results. All women had ovulatory values of progesterone [P≥16.1 nmol/l (LH +6-8)] and normoestrogenemia in the blood (p0.05). According to the results of the correlation analysis, there were no associations between the E2, P levels and the value of M-echo, and no relationships were found between the E2, P levels and the expression of ER, PR, LIF, FOX-proteins. It was revealed that there are significant positive relationships between M-echo and FOXA2 expression in the endometrium (r=0.422; p0.001). Conditional threshold values for the ER, PR expression (LH +6-8) were determined, the excess of which is associated with abnormal expression of LIF, FOX-proteins: for PR in the glands - 105 and 285, for ER in glands - 145, for ER in the stroma - 155. It was found that usual doses of estradiol drugs (1-1.5 mg/day) are capable of increasing endometrial proliferation in women with TE, provided that the expression of ER, PR, LIF, FOX-proteins in their endometrium is similar to healthy women. Increased doses of estradiol drugs (4 mg/day) in women with TE had a significant effect in the form of an increase M-echo value and/or pregnancy in cases where the endometrial expression of LIF, FOX-proteins was comparable with healthy women, even in the presence of hormone-receptor interactions in the endometrium that are different from healthy women. Spontaneous pregnancy in participants of the main group with hypoplastic endometrium in our study occurred in 5 women in whom the expression characteristics of FOXA1 and/or FOXA2 in the endometrium were comparable to healthy women. Conclusion. TE is not the only marker of an imbalance of proteomic molecules, but it determines a greater likelihood of impaired expression of ER, PR, LIF, FOX-proteins in the endometrium. In women with an unclear reason of fertility disorders, it is necessary to conduct an in-depth examination of endometrial samples. Characteristics of endometrial expression ER, PR, LIF, FOX-proteins and the usefulness of hormone-receptor interactions in the TE in women with a history of reproductive disorders can be markers for predicting the effectiveness of the use of exogenous estradiol drugs in women in order to enhance endometrial proliferation with an initially low M-echo.